A Big Data Model for Education Sector - Abdulla Fairuzullah, Ahmad Tajuddin; Noraziah, Ahmad; Mohd Helmy, Abdul Wahab; Haneen, A. A.; Roslina, Mohd Sidek (2017)
Managing a rapidly expanding amount of data involving Information Architecture has long been a goal in many Higher Education institutions. Many have long standing data warehouses and have used analytics tools. As the competition for gifted students becomes more intense while the cost of education makes the pool of potential students more limited, many institutions are taking another look at how they are analyzing potential students and managing the experience that students have while they are enrolled. Analytics play a critical role in performing a thorough analysis of student and learning data to make an informed decision on future course offerings and their mix to cater to the potential and existing students. Big Data systems position Information Technology to see the education becomes more holistically than any other areas for improving the decision making process. Predictive analytics and forecasting models in a Big Data environment enable institutions to make right investment decisions for higher institutional impact and also make the new very high knowledge environment.